Comparison of ventilatory efficacy and airway dynamics between ProSeal laryngeal mask airway and endotracheal tube in adult patients during general anesthesia - Sudheesh Kannan; S S Harsoor; L Sowmiya; S S Nethra; D DevikaRani; M Sathesha (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: Studies have demonstrated minimal hemodynamic variation and postoperative complications with ProSeal laryngeal mask airway (PLMA) compared to endotracheal tube (ETT). Hence, a study was conducted to compare the ventilatory parameters and airway dynamics required to maintain normocarbia and stable hemodynamics with PLMA and ETT. Material and Methods: A prospective, randomized, single blinded study was conducted on 60 patients aged 20-40 years of American society of anesthesiologists class I and II, divided into Group PLMA and Group ETT. Standard anesthesia protocol was instituted. Group PLMA received PLMA sizes as per manufacturer's recommendations and group ETT received appropriate sized cuffed ETT. Patients were initially ventilated at 14 bpm, I:E ratio 1:2, tidal volume (Vt) 6 ml/kg and later adjusted to maintain end tidal carbon dioxide (EtCO 2 ) between 35 and 40 mmHg. Peak airway pressure (Ppeak), compliance (Compl.), Vt, airway resistance (R aw ), hemodynamic parameters, oxygen saturation (SpO 2 ) and EtCO 2 were recorded throughout surgery. Postoperative complications if any, were noted. Results: Demographic parameters, R aw , EtCO 2 , SpO 2 were comparable between groups. Ppeak was lower and Vt needed to maintain EtCO 2 of 35-40 mmHg was lesser in Group PLMA. Compl was low for 5 min after insertion of PLMA. Heart rate was significantly reduced at 1 min post insertion; blood pressures were significantly lower upto 2 min after insertion and post removal in group PLMA. Incidence of cough was significantly lower in group PLMA. Conclusion: ProSeal laryngeal mask airway maintains adequate ventilation at lower Vts and minimal peak pressures, has lesser hemodynamic variations and lower incidence of postoperative cough compared to ETT.